Strategi Pemasaran VIP Airport Service JOUMPA untuk Meningkatkan Jumlah Penjualan di Yogyakarta International Airport - Diva Putri Perdani; Kartika Fajar Nieamah (Sekolah Tinggi Teknologi Kedirgantaraan, 2026)
This research aims to look at effective marketing strategies in the airport VIP service industry, especially at Yogyakarta International Airport. The research method uses a descriptive qualitative approach through SWOT analysis. The data collection techniques used are indept interviews, observation, and documentation. The results showed that the marketing strategy of VIP Airport Service Joumpa at Yogyakarta International Airport has fulfilled the 7P marketing mix indicators (product, price, promotion, place, people, process, physical evidence). In dealing with existing obstacles as responsible staff, joumpa staff will standby and prepare their best service and maintain communication by keeping in touch with customers. Then joumpa staff also maximize their services professionally by carrying out their duties according to procedures. Keywords: Marketing Strategy, VIP Airport Service Joumpa, Sales Volume